2013
DOI: 10.1002/polb.23247
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic model for deformation of polymer nanocomposite melts under large amplitude shear

Abstract: We report the mechanical response of a model nanocomposite system of poly(styrene) (PS)silica to large-amplitude oscillatory shear deformations. Nonlinear behavior of PS nanocomposites is discussed with the changes in particle dispersion upon deformation to provide a complete physical picture of their mechanical properties. The elastic stresses for the particle and polymer are resolved by decomposing the total stress into its purely elastic and viscous components for composites at different strain levels withi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…27 The self-stiffening behavior observed aer multiple deformation stages suggests that stretching and deformation of polymer chains were different in the PMMA composite, and entanglement of chains near particle surfaces can be tuned by oscillatory shear deformation. These recent reported results [26][27][28] on "bare" particle lled polymers guide us to investigate interface effects between graed and matrix chains in LAOS since it is expected that shear ow elds can alter the interpenetration between gras and free chains.…”
Section: Linear Rheology Measurementsmentioning
confidence: 78%
See 1 more Smart Citation
“…27 The self-stiffening behavior observed aer multiple deformation stages suggests that stretching and deformation of polymer chains were different in the PMMA composite, and entanglement of chains near particle surfaces can be tuned by oscillatory shear deformation. These recent reported results [26][27][28] on "bare" particle lled polymers guide us to investigate interface effects between graed and matrix chains in LAOS since it is expected that shear ow elds can alter the interpenetration between gras and free chains.…”
Section: Linear Rheology Measurementsmentioning
confidence: 78%
“…In our previous work on the non-attractive PS-SiO 2 composite system, we have reported that at large strains the polymer deforms similar to polymer networks due to possible stretching of chains between particle clusters and breaking of interconnected particles manifests yielding at intermediate strains. 26 In contrast, in the attractive PMMA-SiO 2 composite where particles are well-dispersed, stress increases monotonically with strain and presents no yielding. 27 The self-stiffening behavior observed aer multiple deformation stages suggests that stretching and deformation of polymer chains were different in the PMMA composite, and entanglement of chains near particle surfaces can be tuned by oscillatory shear deformation.…”
Section: Linear Rheology Measurementsmentioning
confidence: 99%
“…Rheologically, network and dispersion properties have been typically assigned to the slope of the storage modulus G ′ in the terminal regime at percolation for very low angular frequencies. Generally, it is considered that the stress response at small strains is the result of percolated particle network, whereas the large strain behavior is determined by the polymer chain dynamics (Senses and Akcora 2013).…”
Section: Polymer Nanocomposites and Percolationmentioning
confidence: 99%
“…Holt et al also simulated particle–polymer interactions of varying strengths and molecular weights and found that for stronger chain attachment through covalent bonding, particle‐attached chains are stretched near the particle surface, while still entangled with the bulk matrix far away from the surface. Senses and Akcora derived a mechanistic model to predict the elastic stress buildup in polystyrene/silica nanocomposites under LAOS flows and found that the model matches well with experiments when chains near the filler surface are stretched. These results imply that the degree of stretch varies along the attached chain segments during flow.…”
Section: Resultsmentioning
confidence: 86%